2009
DOI: 10.1002/cphc.200900615
|View full text |Cite
|
Sign up to set email alerts
|

From Branched Networks of Actin Filaments to Bundles

Abstract: Cross-linking proteins can mediate the emergence of rigid bundles from a dense branched network of actin filaments. To enable their binding, the filaments must first bend towards each other. We derive an explicit criterion for the onset of bundling, in terms of the initial length of filaments L, their spacing b, and cross-linker concentration f, reflecting the balance between bending and binding energies. Our model system contains actin, the branching complex Arp2/3 and the bundling protein fascin. In the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
(114 reference statements)
1
18
0
Order By: Relevance
“…Accordingly, accumulation of fascin in bridge bundles progresses not in the tip-to-base direction, as in free-edge filopodia (Svitkina et al , 2003), but in a shaft-to-tip manner. Because fascin is believed to be recruited to preformed parallel bundles (Brill-Karniely et al , 2009; Courson and Rock, 2010), the mode of fascin accumulation in bridges supports an idea of bundle assembly in a proximal-to-distal direction. Of interest, fascin arrival to bridges occurs in discontinuous bursts, suggesting a similar mode of bundle formation.…”
Section: Discussionmentioning
confidence: 83%
“…Accordingly, accumulation of fascin in bridge bundles progresses not in the tip-to-base direction, as in free-edge filopodia (Svitkina et al , 2003), but in a shaft-to-tip manner. Because fascin is believed to be recruited to preformed parallel bundles (Brill-Karniely et al , 2009; Courson and Rock, 2010), the mode of fascin accumulation in bridges supports an idea of bundle assembly in a proximal-to-distal direction. Of interest, fascin arrival to bridges occurs in discontinuous bursts, suggesting a similar mode of bundle formation.…”
Section: Discussionmentioning
confidence: 83%
“…Because previous experiments only assessed the architecture of reconstituted actin networks at steady state, these kinetics effects have not been deeply considered despite a long history of studying the morphology of cross-linked F-actin networks 36 . The majority of efforts to understand the morphology of cross-linked actin networks have focused on the role of cross-linker mediated aggregation of filaments with constant length 7,17,23 and the energetic or kinetic constraints of bundling filaments within meshwork 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mathematical modeling of bundle formation in this system supported the convergent elongation mechanism, rather than the tip nucleation model. 52 A strong support for the convergent elongation model of filopodia initiation has been recently provided by in vitro reconstitution of filopodia-like structures self-assembling on supported PI(4,5)P2-containing lipid bilayers in the presence of cytoplasmic extracts. 53 Timeresolved recruitment of individual molecules to filopodia-like structures during their initiation in this system revealed that an F-BAR domain protein Toca-1 is first to be recruited to lipid bilayers through interaction with PI(4,5)P2.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 94%